Green polymer - chitosan as compatibilizing phase in ternary biopolymer blends of polysaccharide and protein - Liu, ChengJun (Nanyang Technological University, 2022)
The purpose of this project is to develop a new polymer blend and investigate its properties through a variety of experiments. Casting and extrusion were used to produce films and bulk polymers of different formulations of starch-zein-chitosan blends containing different amounts of starch, zein, chitosan, and glycerol. Various experiments were conducted to assess the effect of varying compositions on properties. Tensile tests were conducted to determine mechanical properties such as tensile strength, elongation and elastic modulus of the samples. Then water contact angle analysis was performed to determine the physiochemical properties of the samples, including water contact angle. Lastly, X-ray Diffraction was performed to determine the diffraction pattern as well as crystal structure of samples.